Generation of inertia-gravity waves in a baroclinically unstable fluid - Lovegrove, A; Read, P; Richards, C (2000)
A novel technique is used to visualize and measure the baroclinically unstable flow in a two-layer, rotating annulus experiment with very high resolution in space and time. It is found that small-scale, high-frequency waves are generated in certain preferred locations within the flow by a baroclinic wave undergoing amplitude vacillation. These fast waves are investigated in terms of their dispersion relation, and are shown to be consistent with inertia-gravity waves, generated in association with a source moving with the large-scale baroclinic wave. The occurrence of these waves is described and discussed in the context of spontaneous adjustment radiation and the meteorological slow manifold. Phase-portrait analyses of the present experiments indicate that, despite the apparent generation of inertia-gravity waves as spontaneous adjustment radiation, the resulting vacillatory behaviour remains consistent with low-dimensional dynamics.